Experimental study on Fe solubility in vapor-rich hydrothermal fluids at 400–500 °C, 215–510 bar: Implication for Fe mobility in seafloor vent systems. (1st December 2021) - Xing, Yanlu; Scheuermann, Peter; Seyfried, William E.
Abstract: In seafloor hydrothermal systems, vent fluids usually contain elevated dissolved iron (Fe) that is significantly enriched relative to deep ocean seawater. It is commonly thought that Fe is preferentially transported in dense Cl-rich fluids due to the formation of aqueous Fe-Cl complexes. However, Fe enrichment in vapor-rich low-density fluids with low Cl concentrations (<550 mmol/kg) underscores the efficacy of the low-Cl vapor-rich phase to transport Fe in both subaerial and submarine hydrothermal systems. Currently, transport of Fe in low-density vapor-rich fluids is poorly understood due to the lack of high temperature–pressure (T-P) solubility experiments and requisite thermodynamic data. Here, we report new data of Fe solubility from experiments conducted at 400–500 °C, 215–510 bar, targeting fluids with low-density (∼0.1–0.35 g/cm 3 ). The experiments were performed in the KCl-H2 O system with hematite-magnetite and K-feldspar-muscovite-quartz as mineral buffering assemblages. Our results show that Fe solubility positively correlates with density and fluid chlorinity, which are affected by temperature and pressure. The equilibrium constants (log Khm ) for Fe-buffering reaction Fe3 O4 (s) + 2HCl(aq) = Fe2 O3 (s) + FeCl2 (aq) + H2 O were determined. The new data and the data calculated using Helgeson-Kirkham-Flowers (HKF) equation of state were fit into a density model to extrapolate log Khm for hematite-magnetite Fe buffering reaction over a wide T-P range. The density models for magnetite dissolution reaction and pyrite-pyrrhotite equilibrium were also fit based on HKF to allow redox constraints. We show that calculated Fe solubility are in good agreement with measured values in vapor-rich fluids formed via phase separation in mineral buffered and basalt alteration experiments at elevated T-P. The density model was further applied to model Fe transport in fluids at the Brandon hydrothermal field at East Pacific Rise (EPR) 21°S, with T-P constrained by Si-Cl geothermobarometer. The calculations suggest that the reported Fe concentrations of vent fluids at Brandon reflect phase separation occurring at depth in the seafloor, with T-P up to 450 °C, 400 bar, and redox conditions buffered by pyrite-pyrrhotite-magnetite equilibrium.